Remote techniques for hazardous environments proceeding[s] of the international conference. (British Nuclear Energy Society, 1999)
These conference proceedings cover such topics as robotic-assisted distal interlocking; task-directed sensing; remote repair welding of UK Nuclear Power Plants; and Remote detection of (Nuclear) radioactive sources.